S6.5b Genomics and metagenomics of Madurella mycetomatis. (20th September 2022) - Litvintseva, Anastasia; Bakhiet, Sahar; Gade, Lalitha; Bagal, Ujwal; Wagner, Darlene; Siddig, Emmanuel Edwar; Mhmoud, Najwa Adam; Fahal, Ahmed
Abstract: S6.5 Efforts of improving the management of mycetoma: working towards the 2030 goals, September 22, 2022, 4:45 PM - 6:15 PM Mycetoma is a debilitating disease recognized as a neglected tropical disease by the World Health Organization. The etiology of mycetoma is poorly understood; ∼ 60% of cases are caused by fungi and the rest are bacterial, although this varies by region. The pathogenic fungus, Madurella mycetomatis, is most frequently identified in mycetoma cases. Here, we present a high-quality genome assembly of M. mycetomatis and the results of the whole genome sequence analysis of 25 isolates from Sudan. We demonstrate evidence of at least seven genetically diverse lineages and extreme clonality among isolates within these lineages. Shotgun metagenomic analysis of DNA from mycetoma grains confirmed that M. mycetomatis was the predominant causative agent of eumycetoma Sudan; however, 10% of grains also contained bacterial reads suggestive of secondary infections. A thorough understanding of the genetic structure and diversity of fungi causing mycetoma is essential for the development of new diagnostic methods and for identifying potential drug targets.